Does having knowledge of green human resource management practices influence its implementation within organizations? - Vuyokazi Mtembu (Problems and Perspectives in Management, 2019)
Sustainability and green practices are in the frontline of issues organizations globally are concerned about because of the consequences of climate change and its challenges. The objective and key question of this study was to determine whether there is a relationship between knowledge of green human resource management (HRM) practices and its implementation within the organizations. The study followed a methodology of triangulated empirical research approach with a combined method of qualitative and quantitative research approaches. Human resource practitioners from human resource divisions in higher education institutions in KwaZulu-Natal, South Africa, formed the population surveyed. Interview schedule and questionnaires were instruments used in data collection. Thematic analysis was used to analyze data collected from interviews. Statistical Package for Social Sciences (SPSS) version 24 was used to analyze quantitative data collected. About half of HR practitioners indicated minimal awareness of the concept ‘green HRM’, but reflected moderate knowledge and understanding of green HRM activities. Overall, the findings revealed a moderate application of green HRM principles in HRM activities in the institutions. There was no policy framework in the form of green HRM policies to drive green activities within the HR divisions and institutionally. Findings also revealed that there is a relationship between knowledge of green HRM activities and its implementation within the organization. Also, a strong correlation was found to exist between green HRM policies and implementation of green HRM activities in the organization. This then led the researcher to recommend that organizations who aspire to go green, be resource efficient and sustainable will need to have green HRM policies in place, they will also need to ensure that training and awareness workshops on green HRM are conducted to skill and equip all stakeholders involved.